Epidemiology of Leprosy Among Foreign Labors Migrating to Thailand From 1998 - 2016 - เตชะไตรศักดิ์ ชัยรัตน์ (Journal of Preventive Medicine Association of Thailand, 2018)
This research aimed at to study epidemiology of leprosy among foreign labors migrating to Thailand from 1998 2016 after achievement of elimination of leprosy in 1994. As resulted from royal remarks of H.M. King Rama Nine given to members of the Rajpracha Samasai Foundation Committee on Monday, June 2, 1997, the programme on surveillance of leprosy among foreign labors migrating to Thailand has been established and implemented from 1998 2016. The study design is retrospective descriptive clinical epidemiological study of total 559 leprosy cases found among foreign labors as quantitative study together with qualitative articipatory action research study conducted by using open - ended questionnaire to be responded by related 36 administrators, experts and health staffs. Results revealed total 559 leprosy cases found from foreign labors whose 93 percent was from Myanmar with average increasing trends of 19.13 percent per year, together with increasing trend of 16.36 percent per year particularly from 2012 2016. Mean while 10,178 leprosy cases were found from Thai people with decreasing rate of 5.18 percent per year. Clinical pidemiological analysis were performed from such 559 foreign leprosy cases, together with related critical events and factors which were also considered and commented by 36 respondents to the designed questionnaire. Valuable suggestions were made by such respondents and researcher in order to make more effective further studies and improvement of the programme on surveillance of leprosy among foreign labors under royal initiative in the near future, which are vital to the success of sustainable elimination of leprosy and leprosy free as targeted in 2020 by World Health Organization.